Pseudocapsule and pseudocapsule-based extracapsular resection in pituitary neuroendocrine tumors - Wang, Xiao Bin; Han, Tian Yi; Ma, Jian Gong; He, Cheng; Xue, Li; Zhang, Xun; Wu, Zhe Bao (Frontiers in Endocrinology, 2022)
Since Costello et al. proposed the concept of pseudocapsule of pituitary neuroendocrine tumors (PitNETs) in 1936, many studies have been published on its occurrence, development process, histopathology, and morphology. Pseudocapsule has been proposed as the anatomical interface between PitNETs and normal pituitary gland, therefore the so-called pseudocapsule-based extracapsular resection (ER) technique was developed as an extracapsular surgery method for PitNETs,which differs from the conventional intracapsular resection (IR). In recent years, ER has also been widely used in patients of different tumor types, sizes, and age groups, because the pseudocapsule can be identified more clearly under the endoscopy. Endoscopic transsphenoidal resection for PitNETs has become the preferred surgical method. We reviewed relevant literatures in the past 10 years, showing that ER could achieve better rate of gross total resection (GTR) and biochemical remission, and reduce tumor recurrence than IR, without increasing postoperative complications. Therefore, the pseudocapsule and ER should be valued by neurosurgeons and actively promoted clinically.